Can catchment-scale urban stormwater management measures benefit the stream hydraulic environment?. (1st March 2019) - Anim, Desmond O.; Fletcher, Tim D.; Pasternack, Gregory B.; Vietz, Geoff J.; Duncan, Hugh P.; Burns, Matthew J.
Abstract: The potential for catchment-scale stormwater control measures (SCMs) to mitigate the impact of stormwater runoff issues and excess stormwater volume is increasingly recognised. There is, however, limited understanding about their potential in reducing in-channel disturbance and improving hydraulic conditions for stream ecosystem benefits. This study investigates the benefits that SCM application in a catchment have on in-stream hydraulics. To do this, a two-dimensional hydraulic model was employed to simulate the stream hydraulic response to scenarios of SCM application applied in an urban catchment to return towards pre-development hydrologic pulses. The hydraulic response analysis considered three hydraulic metrics associated with key components of stream ecosystem functions: benthic mobilization, hydraulic diversity and retentive habitat availability. The results showed that when applied intensively, the developed SCM scenarios could effectively restore the in-stream hydraulics to close to natural levels. Compared to an unmanaged urban case (no SCMs), SCM scenarios yielded channels with reduced bed mobility potential, close to natural hydraulic diversity and improvement of retentive habitat availability. This indicates that mitigating the effect of stormwater driven hydrological change could result in significant improvements in the physical environment to better support ecosystem functioning. We therefore suggest that intensive implementation of SCMs is an important action in an urbanizing catchment to maintain the flow regime and hydraulic conditions that sustain the 'natural' stream habitat functioning. We propose that stormwater management and protection of stream ecosystem processes should incorporate hydraulic metrics to measure the effectiveness of management strategies. Highlights: Urban development causes alteration to streamflow regime. Altered streamflow regime also impact the in-stream hydraulics. Stormwater control measures (SCMs) can restore altered streamflow regime. Potential to further restore instream hydraulic conditions was evaluated. Applied intensively, SCMs can help to restore the hydraulic conditions.